Improving students' chemical literacy skills through experiential learning on global warming concepts - Sunartri Sunartri; Antuni Wiyarsi; Bambang Susilo (International Journal on Education Insight, 2026)
Improving chemical literacy is an important task in learning in the global and sustainable development era. However, chemistry learning at schools still tends to focus on mastering theoretical concepts. Therefore, a learning model that is able to provide meaningful and contextual learning experience is needed, one of which is the experiential learning model. The experiential learning model is considered capable of facilitating students in constructing knowledge and developing chemical literacy skills. This study aims to analyze students’ chemical literacy skills before and after learning using the experiential learning model on the topic of global warming, as well as analyzing their improvement. This study employed a quasi-experimental method with a one-group pretest–posttest design and was conducted in two public senior high schools in Sleman Regency, Indonesia, with a sample of 144 Grade X students. Data were collected using chemical literacy tests that had been validated theoretically and empirically. The data were analyzed using a paired t-test and N-gain scores. The results showed a significant difference between pretest and posttest scores, with an improvement in chemical literacy skills in the medium category. These findings indicate that the application of the experiential learning model is effective in improving students’ chemical literacy skills on global warming topics.